Orthostatic blood pressure recovery associates with physical performance, frailty and number of falls in geriatric outpatients - Mol, Arjen (J Hypertens, 2021)
Blood pressure (BP) recovery after orthostatic hypotension might be important to prevent cerebral hypoperfusion episodes in older adults, and be related to better clinical outcome. The objective was to study the relationship between BP recovery and clinical outcome, that is physical and cognitive performance, frailty and falls, in geriatric outpatients. METHODS: One hundred and sixty-eight geriatric outpatients underwent continuous (beat-to-beat) BP measurements during standing up, and a comprehensive geriatric assessment, including assessment of physical performance (chair stand test), cognitive performance (Mini Mental State Examination), frailty (Fried criteria) and falls in the previous year. BP recovery was evaluated at 15–30, 30–60, 60–120 and 120–180 s after standing up and defined as mean SBP and DBP in the respective time intervals minus baseline BP. Associations with clinical outcome were assessed using linear (physical and cognitive performance and frailty) and logistic (falls) regression, adjusting for age, sex, baseline BP and initial BP drop. RESULTS: SBP recovery was associated with frailty (30–60 s interval; β = 0.013, P = 0.02) and falls (30–60 s interval; odds ratio = 1.024, P = 0.02). DBP recovery was associated with physical performance (30–60 s interval; β = 0.215, P = 0.01), frailty (30–60 s interval; β = 0.028, P = 0.02) and falls (30–60 s interval; odds ratio = 1.039, P = 0.04). Neither SBP nor DBP recovery was associated with cognitive performance. CONCLUSION: DBP recovery was particularly associated with clinical outcome in geriatric outpatients, suggesting BP recovery to be of clinical interest.